Evolutionary temperature compensation of carbon fixation in marine phytoplankton. (14th February 2020) - Barton, Samuel; Jenkins, James; Buckling, Angus; Schaum, C.-Elisa; Smirnoff, Nicholas; Raven, John A.; Yvon‐Durocher, Gabriel
Abstract: The efficiency of carbon sequestration by the biological pump could decline in the coming decades because respiration tends to increase more with temperature than photosynthesis. Despite these differences in the short‐term temperature sensitivities of photosynthesis and respiration, it remains unknown whether the long‐term impacts of global warming on metabolic rates of phytoplankton can be modulated by evolutionary adaptation. We found that respiration was consistently more temperature dependent than photosynthesis across 18 diverse marine phytoplankton, resulting in universal declines in the rate of carbon fixation with short‐term increases in temperature. Long‐term experimental evolution under high temperature reversed the short‐term stimulation of metabolic rates, resulting in increased rates of carbon fixation. Our findings suggest that thermal adaptation may therefore have an ameliorating impact on the efficiency of phytoplankton as primary mediators of the biological carbon pump. Abstract : The primary production of marine phytoplankton could decline with warming if rates of respiration increase more with rising temperature than photosynthesis. We found that respiration was consistently more temperature dependent than photosynthesis across 18 diverse marine phytoplankton taxa, resulting in universal declines in the rate of carbon fixation with short‐term increases in temperature. Whereas, by contrast, long‐term experimental evolution under high temperature acted to reverse the short‐term stimulation of metabolic rates, resulting in increased rates of carbon fixation.